Utilization of vegetal fibers for production of reinforced cementitious materials - Correia, Viviane da Costa; Santos, Sergio Francisco [UNESP]; Savastano, Holmer; John, Vanderley Moacyr (Rilem Publications SARL, 2017)
Vegetal fibers produced from agroindustrial resources have been used as reinforcement in cementitious materials in the macro, micro and nanometric scales. The cellulosic pulp, besides being used as the reinforcing element, is also the processing fiber that is responsible for the filtration system in the Hatschek method. On the other hand, the nanofibrillated cellulose has the advantage of having good mechanical performance and high specific surface, which contributes to improve the adhesion between fiber and matrix. In hybrid reinforcement, with both micro and nanofibers, the cellulose performs bonding elements with the matrix and acts as stress transfer bridges in the micro and nano‐cracking network, with corresponding strengthening and toughening of the cementitious composite. Some strategies are studied to mitigate the degradation of the vegetal fibers used in cost‐effective and non-conventional fiber cement, as well as to reach sustainable fiber cement production. As a practical example, accelerated carbonation curing at early age is a developing technology to increase the durability of composite materials: it decreases porosity, promotes a higher density in the interface, generating a good fiber–matrix adhesion and a better mechanical behavior. Thus, vegetal fibers are potentially applicable to produce high mechanical performance and sustainable cementitious materials for use in civil construction.
Keywords: Carbonation; Macrofibers; Nanofibrillated cellulose; Pulp; Sustainable fiber cement